Indirect jobs in activities related to coal, peat and oil shale: A RHOMOLO-IO analysis on the EU regions - Giovanni Mandras; Simone Salotti (European Commission, Joint Research Centre (JRC), 2021)
The European Commission is working in order to ensure a smooth transition to cleaner forms of energy production away from fossil fuels in order to meet the EU objective of reaching climate neutrality by 2050. The Just Transition Mechanism was launched to manage this transition, under the European Green Deal. A key information needed to do that is the number of workers who will be impacted by the ongoing decarbonisation process. This technical report contains the RHOMOLO-IO estimates of the number of jobs indirectly related to the energy production industry of coal, peat, and oil shale. These activities directly employ more than 200,000 workers in the EU, and our results suggest that about 140,000 additional jobs are indirectly related to those. This is a significant number that should be considered by the policy makers dealing with the shift away from energy production with fossil fuels.
Keywords: C67; E24; 330; region; growth; Rhomolo; indirect jobs; coal; input-output analysis